Safeguarding children in osteopathic practice part 2: Managing concerns about children. Issue 4 (December 2015) - Feld, A.; Maddick, A.F.; Laurent, S.
Abstract: Osteopaths working with children are likely to encounter child abuse and neglect. In this second of two parts we discuss how to manage safeguarding concerns that may arise in osteopathic practice. We review whether to involve GPs and social services to make informal enquiries and the use of anonymised "what if" conversations. We encourage osteopaths to check family backgrounds and be active in excluding risk. We also discuss practical ethical and legal aspects of consent and confidentiality that can often arise in safeguarding cases. Osteopaths with concerns should feel confident in contacting social workers for a second opinion and for many cases it is not necessary to identify the patient. When details of the patient are communicated, ideally this should be done with the parent's permission to help families in need. In cases where a child may be at risk it may be more appropriate to discuss with a social worker without a parent's or patient's consent. It is the best interests of the child that should guide the osteopath in his management of suspicions of abuse or neglect.